PENINGKATAN HASIL BELAJAR SISWA KELAS IX SMP MELALUI PENDEKATAN EDUKATIF OLEH GURU PENDIDIKAN AGAMA KRISTEN - Masniar Sitorus (Jurnal Christian Humaniora, 2020)
This study aims to find out of the students’ learning outcomes through the educational approach of Christian religious educational teachers. The population are the ninth grade students who are protestant Christian, were 189 students and the sample of this study taken from the population it can be take 25% from 189 they were 47 students. The questionnaire trial was consist of 30 students. The data of research were analyzed using the following steps: Test the relationship obtained by the value of r rxy = 0.832 rtable (α = 0.05, IK = 95%, n = 47) = 0.288, it was found that there was a significant improving of the students learning outcomes through the educational approach of Christian religious educational teachers. The significant relationship test obtained value of tcount = 10,074 ttable (α/2 = 0.025, dk = n-2 = 45) = 2,021 then it is known that there is a significant improving of the students learning outcomes through the educational approach of Christian Religious Educational teachers. Test the coefficient of determination (r2) = 0.692 and the percentage of improving in students learning outcomes through the educational approach of Christian Religious Educational Teachers is 69.2%, there is a positive and significant improving students learning outcomes through the educational approach of Christian religious educational teachers.BAHASA INDONESIA ABSTRACT: Penelitian ini bertujuan untuk mengetahui besarnya peningkatan hasil belajar melalui pendekatan edukatif guru Pendidikan Agama Kristen. Populasi penelitian adalah siswa yang beragama Kristen Protestan sebanyak 189 orang dan sampel penelitian berjumlah 189 x 25% = 47 orang. Uji coba angket dilakukan kepada 30 orang siswa kelas IX SMP. Data penelitian dianalisis dengan langkah sebagai berikut:: Uji hubungan yang diperoleh nilai rrxy = 0,832 rtabel (α=0,05, IK=95%, n=47) = 0,288 maka diketahui terdapat peningkatan  hasil belajar siswa yang signifikan melalui pendekatan edukatif guru PAK. Uji hubungan yang signifikan diperoleh nilai thitung = 10,074 ttabel (α/2 = 0,025, dk= n-2 = 45) = 2,021 maka diketahui terdapat peningkatan hasil belajar siswa yang signifikan melalui pendekatan edukatif guru PAK. suji koefisien determinasi (r2) = 0,692 dan persentase peningkatan  hasil belajar melalui pendekatan edukatif guru PAK adalah 69,2 %, yaitu terdapat peningkatan hasil belajar yang positif dan signifikan melalui pendekatan edukatif guru pendidikan agama Kristen.Keywords: learning outcomes, Christian Religious Educational Teachers